Pemberian Berbagai Dosis Bokashi Jerami Padi yang Difermentasikan dengan PGPR Akar Bambu pada Tanaman Kedelai - Sariyu Erwan; Nurul Istiqomah; Mahdiannoor Mahdiannoor (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2019)
Soybeans will usually grow well at an altitude of no more than 500 to 600 m above sea level. The dry climate is preferred by soybean plants compared to the humid climate. Straw is a vegetative part of rice plants (stems, leaves, pan stalks) that are not collected when the rice plants are harvested. -One of the bokashi rice straw organic fertilizers. Bokashi rice straw contains some essential organic elements needed by plants. Plant Growth Promoting Rhizobacteria (PGPR), is one of the biological agents that has been widely used and tested to control various plant pathogens, utilizing bamboo roots as decomposers because in the bamboo roots there are bacteria Pseudomonas flourescent and Bacillus polymixa which can help the fermentation process. The aim of the study (i) was to find out the effect of giving and (ii) to get the best bokashi rice straw dose on the growth and yield of soybean plants. The study was carried out in Pembakulan Village Batang Alai Timur District, Hulu Sungai Tengah Regency from April to August 2018. This study used a single factor randomized design (RBD), grouping based on sunlight distribution. The factors examined were 4 bokashi rice straw doses (j) consisting of j1 = 1.3 kg per plot, j2 = 2.6 kg plot, j3 = 3.9 kg per plot and j4 = 5.2 kg per plot plot. Factors observed were plant height, leaf number, flowering age, number of pods, number of seeds, and dry weight of 100 soybeans. The results of the study did not indicate the effect of bokashi rice straw on soybean plants.